Loempo Batik Motifs: Visuals Semiotics, Cultural Identity, an Heritage Innovation - Dini Yanuarmi; Rias Wita Suryani; Nofi Rahmanita; Selvi Kasman (Aksara, 2025)
This study aims to analyze Loempo Batik motifs as cultural texts that reflect the intersection of Minangkabau tradition, local identity, and global visual culture. The research employs a qualitative case study approach with a triangulation technique combining interviews, visual documentation, and archival analysis. Data were collected through in-depth interviews with artisans, designers, community leaders, and consumers to obtain comprehensive perspectives. The data were then analyzed using semiotic and multimodal discourse analysis supported by Peirce’s sign theory and visual grammar. The results show that the Rumah Gadang motif serves as a cultural anchor symbolizing Minangkabau heritage; guardian figures such as dragons and Garuda illustrate curated hybridity; while exclusive motifs like Malereng represent forms of cultural resistance. The use of color also carries polysemous meanings that link adat, ecological awareness, and Islamic values. The study concludes that Loempo Batik embodies a model of heritage-based design innovation that balances identity preservation with creative economic development. AbstrakPenelitian ini bertujuan untuk menganalisis motif Loempo Batik sebagai teks budaya yang merepresentasikan persinggungan antara tradisi Minangkabau, identitas lokal, dan budaya visual global. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus dan teknik triangulasi yang memadukan wawancara, dokumentasi visual, serta analisis arsip. Data diperoleh melalui wawancara mendalam dengan perajin batik, desainer, tokoh masyarakat, dan konsumen untuk menggali persepsi dan makna budaya yang terkandung dalam motif Loempo Batik. Analisis data dilakukan dengan menggunakan pendekatan semiotika dan analisis wacana multimodal yang didukung oleh teori tanda Peirce dan tata bahasa visual. Hasil penelitian menunjukkan bahwa motif Rumah Gadang berfungsi sebagai jangkar budaya yang menegaskan identitas Minangkabau; figur penjaga seperti naga dan Garuda menggambarkan hibriditas terkurasi; sedangkan motif eksklusif seperti Malereng mencerminkan bentuk resistensi budaya. Simbolisme warna juga mengandung makna polisemi yang menghubungkan nilai-nilai adat, ekologi, dan Islam. Penelitian ini menyimpulkan bahwa Loempo Batik merupakan model inovasi desain berbasis warisan budaya yang mampu menyeimbangkan pelestarian identitas dengan pengembangan ekonomi kreatif.